2012
DOI: 10.1016/j.jacc.2011.10.888
|View full text |Cite
|
Sign up to set email alerts
|

Catheter-Deliverable Hydrogel Derived From Decellularized Ventricular Extracellular Matrix Increases Endogenous Cardiomyocytes and Preserves Cardiac Function Post-Myocardial Infarction

Abstract: Objectives This study evaluated the use of an injectable hydrogel derived from ventricular extracellular matrix (ECM) for treating myocardial infarction (MI) and its ability to be delivered percutaneously. Background Injectable materials offer promising alternatives to treat MI. While most of the examined materials have shown preserved or improved cardiac function in small animal models, none have been specifically designed for the heart and few have translated to catheter delivery in large animal models. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
319
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 333 publications
(335 citation statements)
references
References 67 publications
9
319
0
Order By: Relevance
“…(41,42) The gel has been shown to retain its gylcosaminoglycan (GAG) content and to allow migration of fibroblasts in vitro. (21) Further studies have demonstrated the ability of the gel to stimulate and allow migration of endothelial and smooth muscle cells in vitro and in vivo in rats. (21,43) It also has a pore size sufficient to promote vasculature infiltration.…”
Section: Acellular Materials Based Scaffoldsmentioning
confidence: 99%
See 2 more Smart Citations
“…(41,42) The gel has been shown to retain its gylcosaminoglycan (GAG) content and to allow migration of fibroblasts in vitro. (21) Further studies have demonstrated the ability of the gel to stimulate and allow migration of endothelial and smooth muscle cells in vitro and in vivo in rats. (21,43) It also has a pore size sufficient to promote vasculature infiltration.…”
Section: Acellular Materials Based Scaffoldsmentioning
confidence: 99%
“…(21) Further studies have demonstrated the ability of the gel to stimulate and allow migration of endothelial and smooth muscle cells in vitro and in vivo in rats. (21,43) It also has a pore size sufficient to promote vasculature infiltration.…”
Section: Acellular Materials Based Scaffoldsmentioning
confidence: 99%
See 1 more Smart Citation
“…ECM hydrogels have been successfully isolated and used in several regenerative medicine applications Valentin et al, 2010;Singelyn et al, 2012). ECMs have been shown to promote tissue healing and regeneration in a number of anatomic locations, including skeletal muscle (Marelli et al, 2010;Mase et al, 2010), oesophagus (Nieponice et al, 2009) and urinary bladder (Boruch et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Injectable hydrogels recently drew media attention as they were shown to be able to repair tissue damaged by a heart attack [15]. Hydrogels that are responsive to specific molecules, such as glucose and antigens, can be used in biosensors [16].…”
Section: Motivation For the Research And Technology Assessmentmentioning
confidence: 99%